Features of the educational process as factors of illusion of knowledge in students - Tkachuk Olha Volodymyrivna (Technium Social Sciences Journal, 2020)
The phenomenon of the illusion of knowledge as a mistake of metacognitive monitoring is considered in the article. The factors of illusion of knowledge that arise in the learning process (use of schemes and presentations, teacher feedback, group interaction, repetition of material, problematization of experience, type of test question, presence or absence of assessment situation) are analyzed. In the process of psychological and pedagogical experiment, the factors that increase the probability of the illusion of knowledge in the educational process of students have been identified